Preparation of nanocomposites based on PMMA and CdSe, CdSe/CdS quantum dots - Stepanova, U. A.; Muradova, A. G.; Al-Mayyahi, H.; Telminov, Evgenii N.; Khakimov, K. T.; Solodova, Tatyana A.; Samsonova, Lyubov G. (Russian physics journal)
Nanocomposites based on PMMA and CdSe, CdSe/CdS quantum dots were developed. Quantum dots (QD) of CdSe, CdSe/CdS with sizes from 2.0 nm to 4.0 nm were obtained by deposition in various media. The photoluminescence range for the obtained QDs was from 480 to 628 nm. The results of the study show that the photoluminescent properties of CdSe, CdSe/CdS quantum dots introduced into the PMMA matrix are retained. The resulting nanocomposites can be used to create solid-state laser active media.